2022
DOI: 10.3389/fspor.2022.847447
|View full text |Cite
|
Sign up to set email alerts
|

Tests and Procedures for Measuring Endurance, Strength, and Power in Climbing—A Mini-Review

Abstract: The interest in climbing is rapidly growing among professional and recreational athletes and will for the first time be included in the 2021 Tokyo Olympics. The sport has also gained increased scientific attention in the past decades. Still, recommendations for testing procedures to predict climbing performance and measure training effects are limited. Therefore, the aim of this mini-review is to provide an overview of the climbing-specific tests, procedures and outcomes used to examine climbing performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Rock climbing performance is highly dependent on the climber’s ability to hang from minimal or hard-to-grasp surfaces or holds ( Bergua et al, 2018 ). Furthermore, several studies suggested that the ability to apply force with the fingers ( i.e., finger strength) is critical in rock climbing performance ( Vigouroux, Goislard de Monsabert & Berton, 2015 ; Saul et al, 2019 ; Stien, Saeterbakken & Andersen, 2022 ). When climbing, various types of grip position can be used depending on the surface or hold characteristics, such as its size, depth, and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Rock climbing performance is highly dependent on the climber’s ability to hang from minimal or hard-to-grasp surfaces or holds ( Bergua et al, 2018 ). Furthermore, several studies suggested that the ability to apply force with the fingers ( i.e., finger strength) is critical in rock climbing performance ( Vigouroux, Goislard de Monsabert & Berton, 2015 ; Saul et al, 2019 ; Stien, Saeterbakken & Andersen, 2022 ). When climbing, various types of grip position can be used depending on the surface or hold characteristics, such as its size, depth, and shape.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently examined factors in climbing performance are anthropometric-, physiological-, psychological- and technical factors (Watts et al, 1993 ; Baláš et al, 2012 ; Saul et al, 2019 ). Among the physiological determinants of climbing performance, it is generally accepted that both maximal strength and local muscular endurance in the finger flexors are the two most crucial components for predicting climbing performance (Grant et al, 1996 ; Watts and Jensen, 2003 ; Watts, 2004 ; MacLeod et al, 2007 ; Baláš et al, 2012 ; Saul et al, 2019 ), despite a variety of testing protocols (Stien et al, 2022 ). For example, specific finger strength and dead-hang duration have been found to explain up to 52 and 70% of the total variance of climbing ability (Baláš et al, 2012 ; Laffaye et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One focus is on performance diagnostics of maximum finger strength and finger endurance, which are very relevant in climbing (MacLeod et al, 2007 ; Baláš et al, 2012 ; Philippe et al, 2012 ; Saul et al, 2019 ). The test protocols used by individual research groups are quite different (Stien et al, 2022 ). Two main variations can be identified: In one variation, participants have to perform sustained isometric contractions ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%